Low Abundances but High Growth Rates of Coastal Heterotrophic Bacteria in the Red Sea - Silva, Luis; Calleja, Maria L.; Huete-Stauffer, Tamara Megan; Ivetic, Snjezana; Ansari, Mohd I.; Viegas, Miguel; Morán, Xosé Anxelu G. (Frontiers in Microbiology, 2019)
Characterized by some of the highest naturally occurring sea surface temperatures, the Red Sea remains unexplored regarding the dynamics of heterotrophic prokaryotes. Over 16 months, we used flow cytometry to characterize the abundance and growth of four physiological groups of heterotrophic bacteria: membrane-intact (Live), high and low nucleic acid content (HNA and LNA) and actively respiring (CTC+) cells in shallow coastal waters. Chlorophyll a, dissolved organic matter (DOC and DON) concentrations, and their fluorescent properties were also measured as proxies of bottom-up control. We performed short-term incubations (6 days) with the whole microbial community (Community treatment), and with the bacterial community only after removing predators by filtration (Filtered treatment Initial bacterial abundances ranged from 1.46 to 4.80 × 105 cells mL−1. Total specific growth rates in the Filtered treatment ranged from 0.76 to 2.02 d−1. Live and HNA cells displayed similar seasonal patterns, with higher values during late summer and fall (2.13 and 2.33 d-1, respectively) and lower in late spring (1.02 and 1.01 d-1, respectively). LNA cells were outgrown by the other physiological groups (0.33 - 1.08 d−1) while CTC+ cells (0.28 - 1.85 d−1) showed weaker seasonality. The Filtered treatment yielded higher bacterial abundances than the Community treatment in all but 2 of the incubations, and carrying capacities peaked in November 2016 (1.04 x 106 cells mL−1), with minimum values (3.61 x 105 cells mL−1) observed in May 2017. The high temperatures experienced from May through October 2016 (33.4 ± 0.4 °C) did not constrain the growth of heterotrophic bacteria. Indeed, bacterial growth efficiencies were positively correlated with environmental temperature, reflecting the presence of more labile compounds (high DON concentrations resulting in lower C:N ratios) in summer.. The overall high specific growth rates and the consistently higher carrying capacities in the Filtered treatment suggest that strong top-down control by protistan grazers was the likely cause for the low heterotrophic bacteria abundances.